Assessment of child behavior in dental operatory in relation to sociodemographic factors, general anxiety, body mass index and role of multi media distraction - Gyanendra Mishra; Seema Thakur; Parul Singhal; Shiv Nath Ghosh; Deepak Chauhan; Cheranjeevi Jayam (Wolters Kluwer Medknow Publications, 2016)
Background and Objectives: Children and adolescents comprise a group of individuals representing a large variation in size, competence, maturity, personality, temperament and emotions experience, oral health, family background, culture, etc. Furthermore, a growing child is in a constant state of flux as he grows up and actively interacts with the environment. Many factors contribute to the dental behavior of the child. The aim of this study was to evaluate the effect of sociodemographic factors, general anxiety, body mass index (BMI), and role of multimedia on the child behavior (CB) in the dental operatory. Materials and Methods: Three hundred and one children aged 3-14 years and their parents participated in the study. In the first visit, the questionnaire was filled by the parent and general examination was done. During the second visit, the required dental procedure was rendered, and the behavior was recorded by a single examiner. Results: Among sociodemographic factors, increasing age is directly related to child's positive behavior, whereas other factors such as gender and socioeconomic status (SES) are not significantly related. General anxiety significantly affects the child's behavior. BMI of the child is not related to child's behavior in dental operatory. Multimedia was not found to be significantly affecting the behavior of the child in dental operatory. Interpretations and Conclusion: The principle conclusion of this study is that there is a significant association of age and treatment procedure rendered with the CB in the dental operatory whereas gender, SES, general anxiety, BMI, and multimedia do not show any significant association with the CB in the dental operatory.